Comparative assessment of backstress models using high-energy X-ray diffraction microscopy experiments and crystal plasticity finite element simulations. (January 2021) - Bandyopadhyay, Ritwik; Gustafson, Sven E.; Kapoor, Kartik; Naragani, Diwakar; Pagan, Darren C.; Sangid, Michael D.
Abstract: Crystal plasticity (CP) models have been evolving since their inception. Advanced experimental characterization methods have contributed significantly to assess the performance and subsequent improvement of many empirical relations in CP, which were directly adopted from classical plasticity theories of solids at the macro-scale. In this research, high energy X-ray diffraction microscopy (HEDM) has been used to track the stress-state of individual grains within a polycrystalline aggregate of a Nickel-base superalloy subjected to cyclic loading. Using path-dependent, mesoscopic stress-states from the HEDM experiment, the performance of two kinematic hardening models, in the context of CP, has been assessed. One of the models is an empirical Armstrong-Frederick equation, and the other is a geometrically necessary dislocation (GND)-based phenomenological model. The results suggest that the GND-based model is capable of capturing the cyclic crystal plasticity response. The present validation efforts are expected to take CP models one step closer towards their implementation in modern engineering workflow. Highlights: Grain average stresses are tracked via high energy X-ray diffraction microscopy (HEDM). Companion crystal plasticity (CP) models are compared to the HEDM results. Different backstress stress formulations are used within the CP models. The geometrically necessary dislocation CP model agrees with the experimental results. The Armstrong-Frederick CP model is only appropriate for symmetric load.